Wartime Housing and Boarding: A Case Study of the Catharine Street North Area of Hamilton, Ontario - Dunkerson, Jennifer (Urban History Review / Revue d'histoire urbaine)

(untitled) (Urban History Review / Revue d'histoire urbaine, 1992)
In this study of boarding during World War II, new primary source material is used to reveal a tendency for necessary boarding arrangements in overcrowded, industrial, urban areas. The names, occupations and marital status of boarders were included in the tax assessment rolls for the city of Hamilton in the years spanning 1939 to 1951. Based on contemporary housing studies and more recent analyses of housing and boarding in our industrial past, a correlation may be found between the existence of boarders in a specific area of Hamilton and the nationwide trends of housing shortage, family formation, and wartime production.